ENTREPRENEURSHIP MAHASISWA FAKULTAS EKONOMI - Kun Ismawati; dewi pujiani (Universitas Sahid Surakarta, 2014)
his research aimed to analyze the point of view about entrepreneurship of students in economic faculty. Respondents of this research were many students in alleconomic colleges/ universities in Surakarta. This case study analyzed with regression analysis. The research result showed that desire in business and support of family andsocial life have a positive and significant influence in entrepreneurship decision making of economics students after graduated. Support of family and social life was the mostdominant factor in their entrepreneurship decision making.